Earnings management opportunistic or efficient in Pakistan? The role of corporate governance practices - Syed Farhan Shah; Shahid Mehmood; Muhammad Asif Khan; József Popp (Cogent Business & Management, 2024)
This study empirically investigates how companies listed on the Pakistan Stock Exchange (PSX) manage their earnings from 2010 to 2019. It also examines the impact of Corporate Governance (CG) on the choice of Earnings Management (EM) strategies among these companies. The study employs data from companies listed on the PSX during the period from 2010 to 2019 to test these relationships. Researchers in current research used discretionary accrual as proxy to measure the EM by using the model that was modified by Jones. Future probability is measured a year ahead cash flow taken from operation, that is, a year ahead discretionary income and a year ahead earnings' change. To conduct empirical analysis the researchers estimated Feasible Generalized Least Square (FGLS) and results of study revealed that earnings management in the firms selected from Pakistan Stock Exchange have opportunistic earnings management approach. Researchers found that there is a weak but significant impact of managerial ownership for the type of EM. Organizations which have a high level of managerial ownership are found efficient in EM as compared to rest of types of ownership. Contrarily, it has been found that there is not any significant evidence for institutional ownership (IO), Family Ownership (FO), larger board (LB), independent board (IB) and Firms with high ratio of independent directors for audit committee to engage in efficient level of EM. The finding has implications for policymakers and regulators to place additional monitoring on firms to control opportunistic earnings manipulations.
Keywords: 650; Type of earnings management; corporate governance; feasible generalized least square (Fgls); future profitability; pakistan